IMPROVEMENT OF STATE REGULATION OF ROAD SAFETY IN RUSSIA: COMPARATIVE ANALYSIS OF EXPERIENCE OF THE RUSSIAN FEDERATION AND THE REPUBLIC OF BELARUS - A. Pavlyukova (Вестник Северо-Кавказского федерального университета)
The use of acmeological approach by researchers of human capital is connected with the new role of human capital in conditions of innovative economy. In the article the concept of professional acme is added to the discussion on innovative activity of human capital. It allowed to consider socially significant professional acmes as qualitative characteristic of the human capital of innovative economy - set of subjects (actors) of innovative transformations, and personal professional acmes as characteristic of human potential of innovative economy that it creates the reasons for use of akmeologichesky tools for assessment of a personnel component of innovative potential of economic systems. The composition of acmeological technologies and methods of development of human capital of the innovative economy is expanded by the inclusion of: creation of acmeologically saturated professional environment and presence of akme-events, which can become an impetus in professional development, creating external conditions of appearance of akme in professional development and raising the level of human capital of the innovative economy.